PEMIKIRAN FAZLUR RAHMAN TENTANG PENDIDIKAN DAN RELEVANSINYA DALAM DUNIA MODERN - Dwy Purwaningsih (PAI RAFAH, 2019)
Pragmatic education thought-instrumental is a philosophic point of view that blends with the religious viewpoint of abstract speculation in outlining the education. One of renewing Islamic education is Fazlur Rahman. According to him, the goal of Islamic education are as renewal which is the initial step in the Islamization for all aspects of human life. The study of library (library research) i.e. research sourced from material libraries using a qualitative approach. In this case, the author does exploration of a number of primary data as well as secondary data. The author does an analysis of the concept of Islamic education prespective Fazlur Rahman and relevance against the modern world. The concept of educational thought Fazlur Rahman i.e. the Qur'an as a guide in resolving every problem and the answer and make the human person that are creative, have moral values in accordance with the Qur'an. Whereas, education as an alternative to the secular science by receiving updates and tried to enter it with Islamic concepts as for Islamic education renewal effort started from the educational objectives, educational system, learners, educators and the means of education. The relevance of educational thought on modern world Fazlur Rahman now is integration between religion and discrimination through public education, omission of religion and public education, this has been done wrong by the College namely IAIN with try to follow the thinking of education Fazlur Rahman dare change the State Islamic University (UIN).